2006
DOI: 10.1097/01.blo.0000218748.30236.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Total Hip Design on Dislocation

Abstract: Dislocation following hip arthroplasty remains problematic. While the etiology of dislocation may be multifactorial, implant system design may play a role. Using a computer aided design program, virtual range of motion of several commonly implanted designs was performed with prosthetic interference representing impingement used as an endpoint. Implants with small diameter head size (22 mm) and a larger trunion geometry (type II taper) demonstrated impingement in flexion at less than 90 degrees , suggesting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The results of this study show that the contralateral side is the most accurate template for the reconstruction of the femoral offset for both men and women. Where the contralateral side cannot serve as a template, the FO values measured and the correlation found in our study might help to identify possible reasons for symptoms that occur postoperatively, as FO has been shown to be closely linked to the incidence of a variety of alterations [1, 3, 4, 17]. …”
Section: Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of this study show that the contralateral side is the most accurate template for the reconstruction of the femoral offset for both men and women. Where the contralateral side cannot serve as a template, the FO values measured and the correlation found in our study might help to identify possible reasons for symptoms that occur postoperatively, as FO has been shown to be closely linked to the incidence of a variety of alterations [1, 3, 4, 17]. …”
Section: Limitationsmentioning
confidence: 92%
“…These values also make it possible to quantify the changes in hip geometry. Finally, index joint geometry values for FO are needed as well for a correct diagnostic evaluation of postoperative complications such as early hip joint dislocation [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…In a recent report on a consecutive series of 254 primary hip arthroplasties performed by a single surgeon Padgett et al , reported a 4.8% rate of dislocation at a minimum followup of 2 year. Stratified by head size, the dislocation rates were 3.6% for 28-mm, 4.8% for 26-mm, and 18.8% for 22-mm bearings 52. Patients who are at higher risk for dislocation will have a less likely chance of complications with a larger head.…”
Section: Risk Factorsmentioning
confidence: 93%
“…The reduced risk of dislocations (Beaule et al 2002, Burroughs et al 2005, Padgett et al 2006) allows patients with large articulations unrestricted movement postoperatively. It causes the patient less anxiety (Nissen et al 2011) and permits more intensive training, which has led to faster recovery when using the anterolateral approach (Kuijer et al 2009, Sharma et al 2009).…”
mentioning
confidence: 99%